2017
DOI: 10.1007/s10803-017-3245-7
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Autistic Traits in Preschool Children and Later Emotional/Behavioral Outcomes

Abstract: Although children with a greater number of autistic traits are likely to have other mental health problems, research on the association between earlier autistic traits in preschool children and later emotional/behavioral outcomes is scarce. Using data from 189 Japanese community-based children, this study examined whether autistic traits at age 5 were related to emotional/behavioral outcomes at age 7. The results showed that prior autistic traits were subsequently associated with all emotional/behavioral domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 62 publications
2
32
0
Order By: Relevance
“…Participants in this study comprise a subsample of an ongoing longitudinal study, the Tama Children’s Survey (TCS). In 2011, the TCS was started to explore autistic symptom distribution and functional outcomes in childhood by targeting a cohort of community children ( N = 461) living in the Tama District of Tokyo, Japan, that has been previously described elsewhere (Kamio et al 2014 ; Saito et al 2017 ). This report concerns the subsample whose prospective data sets at age 5 and 8 were complete, including information on sociodemographic status (SES).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in this study comprise a subsample of an ongoing longitudinal study, the Tama Children’s Survey (TCS). In 2011, the TCS was started to explore autistic symptom distribution and functional outcomes in childhood by targeting a cohort of community children ( N = 461) living in the Tama District of Tokyo, Japan, that has been previously described elsewhere (Kamio et al 2014 ; Saito et al 2017 ). This report concerns the subsample whose prospective data sets at age 5 and 8 were complete, including information on sociodemographic status (SES).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, there is also some evidence that the negative effects of these traits may stretch across time. For example, a recent longitudinal community-based study showed that emotional symptoms and peer problems in schoolchildren aged 7 years were predicted by higher autistic traits assessed at age 5 (Saito et al 2017 ). However, to the best of our knowledge, as yet, no study has examined whether autistic traits in the general population remain stable during the transition period from preschool to elementary school.…”
mentioning
confidence: 99%
“…The latter is sometimes referred to as a ‘preference for sameness’ which may be so intense as to be described as an ‘insistence’ on sameness (Szatmari et al, 2006), and is evident when these children are required to change from one task to another (referred to as a ‘transition’), a process that is often accompanied by stress, agitation, and challenging behaviour (APA, 2013). As well as being a key diagnostic indicator of ASD, this resistance to change tasks has been shown to negatively impinge upon academic and social interaction success in children with ASD (Dunlap et al, 1983; Hsiao et al, 2013; Saito et al, 2017; Wolery et al, 1985), principally because of their difficulty in making the required transitions to different learning tasks that occur within the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Although most previous reports have referred to parental evaluations of their child's stress and anxiety regarding task transitions (e.g., Hsiao et al, 2013; Saito et al, 2017), the key indicator of physiological stress arousal that is also a major component of anxiety is the response of the autonomic nervous system (ANS) (Hall, 2016). The ANS acts through two subsidiary systems: the sympathetic (SNS) and the parasympathetic (PNS) nervous systems, with the SNS being the primary indicator of response to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with high autistic traits were found to be at higher risk for psychological disorders (e.g., anxiety and depression) [Liew, Thevaraja, Hong, & Magiati, 2015], and behavior problems (e.g., social problems and withdrawn behavior) [Hoekstra, Bartels, Hudziak, Van Beijsterveldt, & Boomsma, 2007]. It is important to identify children who may be at risk for ASD to allow for early identification and support and better subsequent emotional or behavioral outcomes [Saito et al, 2017]. Therefore, there is a growing demand for reliable instruments to quantify autistic traits and screen for highrisk children.…”
Section: Introductionmentioning
confidence: 99%